EXPERIMENTAL STUDY OF SYNTAXIAL VEIN GROWTH DURING LATERAL FLUID FLOW IN TRANSMITTED LIGHT: FIRST RESULTS - Hilgers C.; Urai J.L. (My University, 2002)
In-situ observations of transmitted-light experiments of syntaxial vein growth during lateral fluid flow in a simulated fracture show a decrease in growth rate towards the downstream end. As a consequence, the fracture is sealed at the inlet. Our observations show the rapid, non-linear growth competition of grains, which is a result of anisotropic growth kinetics and the complex fluid flow around the individual crystals.We compared our results with simulations based on a simplified numerical model, which builds on existing simulation techniques of this system. The model incorporates plug flow and a fluid-flow velocity dependent crystal growth rate law based on literature data. Simulations are in reasonable agreement with experimental results. A sensitivity analysis shows that a high fluid flow velocity and a low supersaturation increase the potential to seal a vein homogeneously, in agreement with previous work. Additionally, the effect of the initial crack shape is explored.